HUBUNGAN ASUPAN ZAT BESI, ASAM FOLAT, VITAMIN B12 DAN VITAMIN C DENGAN KADAR HEMOGLOBIN SISWA DI SMP NEGERI 2 TAWANGHARJO KABUPATEN GROBOGAN - Arenda Reka Narima Septyasih; Laksmi Widajanti; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Anemia is a decrease in the number of red cell mass or hemoglobin mass that it can not fulfill its function is to carry oxygen in sufficient quantities to peripheral tissues. Disruption of the formation of red blood cells can be caused by food consumed less containing nutrients, especially essential nutrients such as iron, folic acid, vitamin B12, protein and vitamin C. Prevalence of Anemia in Grobogan District in 2015 amounted to 30.9%. This study aimed to analyze the relationship between the intake of iron, folic acid, vitamin B12 and vitamin C with hemoglobin levels of students in Junior High School 2 Tawangharjo Grobogan District. Type used observational research with cross-sectional approach. The data collection is done with recall 24 hours over two days in a row and hemoglobin content value obtained from venous blood sampling method Sahli and corrected by the method Sianmethemoglobin. The total sample of 70 samples were taken using stratified random sampling is done randomly by lottery. The correlation test used is the Spearman rank correlation. The results showed that the intake of iron, folic acid, vitamin B12 and vitamin C intake of the majority of research subjects including less category. 67.1% iron intake, intake of folic acid 77.1%, 65.7% intake of vitamin B12, vitamin C intake as much as 52.9% and 75.7% suffering from anemia. The result of the correlation intake of iron, folic acid, vitamin B12 with hemoglobin levels obtained value of p <0.05 and correlation of test results vitamin C content of hemoglobin obtained value of p> 0.05. There is a relationship intake of iron, folic acid, vitamin B12 with hemoglobin levels of students in Junior High School 2 Tawangharjo Grobogan District. And there was no association of vitamin C intake with hemoglobin levels of students in Junior High School 2 Tawangharjo Grobogan District.